When Violence Can Appear With Different Male Partners: Identification of Resilient and Non-resilient Women in the European Union - Herrero, Juan; Vivas, Pep; Torres, Andrea; Rodríguez, Francisco J. (Frontiers in Psychology, 2018)
Introduction: Little scholarly attention has been paid to the analysis of the history of intimate partner violence (IPV) against women with different male partners and how it could be related to levels of IPV with the current male partner. From this point of view, been a victim of IPV could increase the vulnerability of women and, therefore, exert a negative influence on the selection of partners over time, thus increasing the odds of potentially mating with abusive male partners. Alternatively, for some women victims of IPV in previous relationships, there may be additional resources that reduce their vulnerability to victimization by new partners. Methodology: The present study analyzes levels of IPV in different partners of 2376 heterosexual women from the 28 countries of the European Union living together as a couple who had previously lived with a different male partner. Analysis/Discussion: Multilevel regression results indicated that resilient women were younger, more satisfied with household income, and were involved in shorter relationships. As for their previous levels of victimization, they scored lower on child abuse and non-partner adult victimization. Also, their levels of victimization from previous partners were the same as those of the non-resilient women, with the exception of physical IPV victimization where resilient women scored higher than non-resilient women. Resilient women also informed the interviewer to have ended the abusive relationship because of the violence to a greater extent than non-resilient women and seemed to suffer fewer psychological difficulties due to previous violent relationships. Finally, countries scoring higher on human development index (HDI) showed a larger proportion of resilient women. Conclusion: Resilient women are mostly characterized by fewer psychological difficulties and lower frequency of adverse situations (in childhood or in adulthood) when compared to non-resilient women. Although resilient women reported a higher physical IPV, they nevertheless show fewer psychological sequelae and a greater ability to end abusive relationships. In addition, the human development of the countries in which they live also seems to reinforce their resilience, which suggests combining intervention policies at the individual and contextual levels.